Urticarial vasculitis induced by OTC diet pills: a case report - Cherrez-Ojeda, Iván; Loayza, Enrique; Greiding, Leonardo; Calderón, Juan Carlos; Cherrez, Annia; Adum, Farid (World Allergy Organization journal, 2015)
Background Urticarial Vasculitis (UV) is in most of the cases idiopathic; however it has been associated with several conditions and drugs. Over the counter (OTC) diet pills are widely available, even on-line, but they are rarely regulated by pharmaceutical control. Case presentation We present the case of a 35-year-old female patient suffering of pruriginous and painful wheals more than 1 cm in diameter, with a burning sensation. The eruption lasted more than 24 hours and was accompanied by angioedema, headache and myalgia. No remarkable medical history was found, except for previous intake of OTC diet pills. UV diagnosis was confirmed by the skin biopsy of a lesion. Conclusion OTC diet pills are widely available worldwide, and due to its widespread use, allergologists and dermatologist should be able to recognize symptoms and lesions of cutaneous vasculitis, which may be under reported.
Gesehen am 16.11.2020